Global Patterns and Drivers of Litter Decomposition Under Nitrogen Enrichment: A Meta-Analysis - Su, Yuan; Ma, Xiaofei; Gong, Yanming; Ahmed, Zeeshan; Han, Wenxuan; Li, Kaihui; Liu, Xuejun (Frontiers in Forests and Global Change, 2022)
Nitrogen (N) enrichment has substantially altered terrestrial litter decomposition, with positive, neutral and negative effects. However, general pattern and drivers of how global litter decomposition responds to N enrichment rates remain limited and how litter decomposition, especially in different ecosystems, changed with differential N enrichment rates still need to be answered. Here, this study reviewed 118 published papers of litter mass remaining after N enrichment to assess the influences of relevant environmental and experimental factors on the relationships between N enrichment and litter decomposition in grassland, forest, and wetland ecosystems. Results indicated that N enrichment had non-significant effect on global litter decomposition. However, the effects were greatly variable among ecosystem type, with an increase in litter decomposition by 3.91% in grassland and by 1.82% in wetland and a decrease in litter decomposition by 1.23% in forest. When forest was further grouped into plantation, primary and secondary forest, results showed that N enrichment significantly slowed litter decomposition rate by 2.96% in plantation and did not significantly influence litter decomposition in primary and secondary forest. The effect magnitude and direction of N enrichment are regulated by experimental and environmental factors. Specially, mixed N enrichment (for example, urea and glycine) exhibited stronger effects on litter decomposition relative to single N fertilizer. Our findings indicated that the divergent responses of litter decomposition in forest and grassland, which will greatly advance our ability to accurately evaluate and predict global C cycling under increased N enrichment, and should be considered and applied in global biogeochemical models.